Peran Guru BK dalam Meningkatkan Aktivitas Belajar Siswa - Rullo, Jilan Maulidya (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The aim of this case study is the role of teacher knowledge in improving student learning activities. The method used in this activity is the qualitative descriptive method. The instrument used is using data collection techniques which are carried out by triangulation or combining by analyzing qualitative data. The qualitative data collection method in this research is qualitative analysis by conducting case studies from literature reviews resulting from field research which are analyzed using a qualitative descriptive approach. Based on the results of the case studies of the three articles described, it can be said that the role of guidance and counseling teachers is very important in helping students to deal with the problems that students are facing. It is hoped that the guidance from the counseling teacher can help students to be more active in their learning activities, so that learning goals are achieved.